2007
DOI: 10.1007/s00436-007-0755-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and differential expression of manganese superoxide dismutase (Mn-SOD) of Trichinella pseudospiralis

Abstract: The complete coding sequence of manganese superoxide dismutase (Mn-SOD) of Trichinella pseudospiralis (Tp) was obtained and characterized for the first time by degenerative reverse transcription polymerase chain reaction (RT-PCR) and rapid amplification of complementary DNA ends (RACE) reactions. The open reading frame of Tp Mn-SOD contained 663 nucleotides, encoding 220 amino acid residues. This included the conserved histidine and aspartate residues for metal binding, cysteine residues for disulfide bond for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The manganese SOD of T. pseudospiralis was reported by Wu et al (2007a). This manganese SOD is a mitochondrial enzyme because of the presence of mitochondrial transit peptides and maturation cleavage site in this protein.…”
Section: Superoxide Dismutasesmentioning
confidence: 99%
“…The manganese SOD of T. pseudospiralis was reported by Wu et al (2007a). This manganese SOD is a mitochondrial enzyme because of the presence of mitochondrial transit peptides and maturation cleavage site in this protein.…”
Section: Superoxide Dismutasesmentioning
confidence: 99%
“…Our previous study of the Cu/Zn-SOD of S. erinacei suggested that its primary role in parasite survival was in protecting the parasite from endogenous oxidative stress as well as detoxifying exogenous superoxide anions (Li et al, 2010). Compared with the extensive work that has been performed on the Cu/Zn-SODs of helminth parasites, only a few helminth Mn-SODs have been identified (Henkle-Dü hrsen et al, 1995;Li, Kong et al, 2005;Wu et al, 2008), and information on their biochemical and biological properties is limited. Considering the mitochondrial erinacei.…”
Section: Discussionmentioning
confidence: 99%
“…These studies collectively suggest the critical roles that mitochondrial SODs play in the maintenance of cellular physiology. It is well known that the extracellular and cytosolic SODs (mostly Cu/Zn-SODs) of helminth parasites play essential roles in parasite survival in the host by detoxifying superoxide anions produced endogenously by the parasite as well as the host immune effector cells (Henkle et al, 1991;Hong et al, 1992;Tang et al, 1994;Kim et al, 2000;Piedrafita et al, 2000;Tawe et al, 2000;Castellanos-Gonzá lez et al, 2002;Li, Na et al, 2005;Li, Kong et al, 2005;Lee et al, 2005;Wu et al, 2006). Our previous study of the Cu/Zn-SOD of S. erinacei suggested that its primary role in parasite survival was in protecting the parasite from endogenous oxidative stress as well as detoxifying exogenous superoxide anions (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play essential roles in protecting organisms from oxidation by the superoxide anion which is produced by enzymatic and non-enzymatic metabolic pathways (Fridovich 1998). SODs have been identified and characterized in various helminth parasites, and their essential roles for parasite survival in the hosts have been well addressed (Henkle et al 1991;Hong et al 1992;HenkleDührsen et al 1995;Kim et al 2000;Tawe et al 2000;Castellanos-González et al 2002;Lee et al 2005;Li et al 2005a, b;Wu et al 2008). Several studies have also suggested the potential of SODs of parasitic helminths as vaccine candidates (Shalaby et al 2003;Carvalho-Queiroz et al 2004;Cook et al 2004;Vaca-Paniagua et al 2008).…”
Section: Introductionmentioning
confidence: 99%